Life and Works of Saint Gregentios, Archbishop of Taphar Introduction, Critical Edition and Translation - Berger, Albrecht (Millennium-Studien / Millennium Studies, 2012)
In the late 10th century, an anonymous author wrote the fictitious account of a religious dialogue between Archbishop Gregentios and the Jewish scribe Herban and included it in a life of Gregentios based on earlier sources, which indicate that he was a missionary in Yemen in pre-Islamic times. Albrecht Berger examines and translates these texts, and he presents a critical edition. Key Features first edition of a large proportion of the extant texts critical edition using all known manuscripts, including those which only recently have been discovered